Answer:
g(n) = - 29
![(-4)^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ei0ifhrbaljwlz7kijm51s7ippfmm3x2sr.png)
Explanation:
Given the recursive formula
g(n) = g(n - 1). - 4
This tells us that to obtain a term in the sequence we multiply the previous term by - 4.
We are dealing with a geometric sequence with explicit formula
g(n) = g(1)
![(r)^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ez8dud9slpmkhrs6kdah0v4b69qcdaapqa.png)
Here g(1) = - 29 and r = - 4, thus
g(n) = - 29
← explicit formula